Case Report: SCOUT MD™ four reflector technology—enhancing accuracy in breast lesion isolation - LaRussa, Anna; Caputo, Sydney; Sadeghi, Ali; Corsetti, Ralph (Frontiers in Surgery, 2025)
We present a novel approach for localizing a large, non-palpable area of ductal carcinoma in situ (DCIS) for surgical resection using multiple SCOUT reflectors in a 45-year-old woman with DCIS of the left breast. Lesional resection using SCOUT MD™'s four unique reflectors was completed with real-time feedback from the SCOUT probe, providing information on distance, depth, and orientation around the perimeter of the calcifications. Successful DCIS resection was confirmed by post-resection tomosynthesis imaging of the partial mastectomy specimen, and negative margins were achieved. The patient synchronously chose contralateral breast reduction to achieve symmetry with the ipsilateral oncoplastic reduction mastoplasty. Advancements in SCOUT MD™ technology provide for improved intraoperative precision in the dissection with the use of four unique reflectors, while maintaining optimal cosmetic results by minimizing the removal of normal tissue. We believe these technological advancements in breast tumor localization will reduce rates of re-excision and the need for additional surgical management.